1998
DOI: 10.1017/s0950268898001460
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the occurrence of sporadic Salmonella enterica serotype enteritidis infections in children in France: a national case-control study

Abstract: To determine risk factors associated with the occurrence of sporadic cases of Salmonella enteritidis infections among children in France, we conducted a matched case-control study. Cases were identified between 1 March and 30 September 1995. One hundred and five pairs of cases and controls matched for age and place of residence were interviewed. In the 1-5 years age group, illness was associated with the consumption of raw eggs or undercooked egg-containing foods (OR 2.4, 95% CI 1.2-4.8). Storing eggs more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 10 publications
3
32
1
Order By: Relevance
“…This applies to chicken meat as direct source of infection as well as infections from secondary contamination [8]. The main focus of preventive measures should be directed at reducing the danger of infection caused by consuming eggs [9][10][11][12]. The PT 36 outbreak described in this paper further corroborates this conclusion.…”
Section: Discussionsupporting
confidence: 68%
“…This applies to chicken meat as direct source of infection as well as infections from secondary contamination [8]. The main focus of preventive measures should be directed at reducing the danger of infection caused by consuming eggs [9][10][11][12]. The PT 36 outbreak described in this paper further corroborates this conclusion.…”
Section: Discussionsupporting
confidence: 68%
“…As for a previous study [7], we summarized the exposure to raw eggs and to food containing raw or lightly cooked eggs as a composite, unique variable. Among case patients and control subjects who ate eggs, 24 case patients (27%) and 43 control subjects (48%) reported eating raw eggs or food containing raw or lightly cooked eggs (OR, 0.4; 95% CI, 0.2-0.8).…”
Section: Resultsmentioning
confidence: 99%
“…The negative association between consumption of raw eggs, consumption of bivalve molluscans, and S. typhimurium infection in univariate analysis may illustrate an information bias. Our experience [7] indicates that many parents are aware of the risk of gastroenteritis posed by the consumption of these foods and may answer that they did not serve these foods, even though they might have done so.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Available information revealed that most of the infants were either breastfed for a period of one to three months or in some cases, not breastfed at all but mostly fed with baby food cereals. Studies elsewhere have demonstrated that infants infected with Salmonella are less likely to be breastfed and more likely to have a household member with diarrhoea than healthy infants [23][24][25], situations that could not be ruled out in this study. A report from northern Nigeria had implicated young adults within the 11 to20 years and 21 to 30 years age groups to be the most vulnerable members of the community [7].…”
Section: Discussionmentioning
confidence: 96%